maths question

  • 1 vote

 1)              x/4 + 1 = x/3

 2)              (2x+5)/3 = (3x-1)/4

thankss guyss.. really..

i just need to know the answers to these two questions =)

Posted Sun 5th June, 2011 @ 12:19 by Anam

15 Answers

  • 1 vote

ermm why is my question voted down ??

Answered Sun 5th June, 2011 @ 12:33 by Anam
  • 1 vote

i got 23 for the second one too !! :D

**** for the first one i got 3.. one of us is worng.. i dont know how to gett the right answer :(

Answered Sun 5th June, 2011 @ 12:39 by Anam
  • 1 vote

i'm really confused! is the first question: 

x/(4 + 1) or (x/4) + 1?

Answered Sun 5th June, 2011 @ 12:44 by Kelly:)
  • 1 vote

second question is 23 i agree

Answered Sun 5th June, 2011 @ 12:46 by Chloe Thorn
  • 1 vote

i hope its 3

i did it differently

i timesed both the sides by 12

that took away the denominators becoming 3(x+1) = 4(x)

and then expandd and work outt normallyy.. wat do u thiink ?

Answered Sun 5th June, 2011 @ 12:47 by Anam
  • 1 vote

yeah that seems to make sense :)

Answered Sun 5th June, 2011 @ 12:49 by Kelly:)
  • 1 vote

sooo dod u guys thiink itss 3 or 12 ?

Answered Sun 5th June, 2011 @ 12:49 by Anam
  • 1 vote

yep, silly me!! lol

I think thats the right (and not blonde) way to do it!! hee hee

Answered Sun 5th June, 2011 @ 12:50 by Emma
  • 1 vote

the first question is (x/4) +1

Answered Sun 5th June, 2011 @ 12:51 by Anam
  • 1 vote

no its 12

x/4   + 1= x/3

 times all terms by 3

3x/4+3=x      

times all terms by 4

3x+12=4x      

take away 3x   

12=x

Answered Sun 5th June, 2011 @ 14:51 by Pui Pui
  • 1 vote

1.) Re-arrange:

1 = x/3 - x/4

1 = 4x-3x/12

1=x/12

12=x

2.) Cross multiply:

4(2x+5) = 3(3x-1)

8x + 20 = 9x - 3

20 + 3 = 9x - 8x

23 = x

Answered Sun 5th June, 2011 @ 21:30 by N. M
  • 0 votes

for the first one i got: x = -4:

3x/4+1 = x

3x = 4x + 4

-4 = x

for the second one i got: x = 23:

8x + 20 = 9x - 3

23 = x

not entirely sure if they're right but they're my answers :) x

Answered Sun 5th June, 2011 @ 12:36 by Kelly:)
  • 0 votes

i think this is right for question one

1) first times the equation by  4 to get x+1=4x/3

2)then times the equation by three to get 3x+3=4x

3) then take away 3x to give you 3=x

the only thing i am unsure of is if i need to times the one by 4 in the first step and if that need to happen you would get 12 as the answer as you would have x+4 =4x/3 then 3x+12=4x and x=12

 i would go with 12 as the answer to question one - feel free to correct me if i am wrong guys ! 

Answered Sun 5th June, 2011 @ 12:40 by Chloe Thorn
  • 0 votes

I got x=o.5 or 1/2 for number 1.

x/4 + 1 = x/3

x+1 = 4x/12

x+1 = 3x

1 = 2x

2x = 1

 x = 0.5 or 1/2

Answered Sun 5th June, 2011 @ 12:45 by Emma
  • 0 votes

its three! that makes so much more sense now :)

Answered Sun 5th June, 2011 @ 12:51 by Kelly:)